El Salvador - Public Expenditure Review : Enhancing the Efficiency and Targeting of Expenditures, Volume 2. Chapters and Statistical Tables - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER), produced jointly by the World Bank and the Inter-American Development Bank (IADB), is an in-depth economic and sector report on El Salvador. The study builds on the analysis and recommendations of the PER delivered in 2004 that concluded that El Salvador faced the dual challenge of addressing deteriorating fiscal trends while financing key investments required to accelerate growth and meet pressing social needs. This report is intended to provide the government with practical and useful near-and medium-term recommendations that will support the country's efforts to ensure sustainable fiscal balances and establish effective and transparent mechanisms to allocate public resources to promote broad-based economic growth, improve social indicators, and reduce poverty. Hence, the government knows that El Salvador is faced with two fiscal challenges that will have great influence on the economic performance over the coming years. The first is the need to improve the fiscal balance, by strengthening revenue and reducing expenditure, to ensure medium-term sustainability. The second is the need to finance priority investments required to accelerate growth, reduce unemployment, and cover basic social needs. Meeting both challenges simultaneously will require great skill, given the still fragmented political environment and the difficulties in creating a consensus on future policies. The country needs to strengthen its fiscal stance because not doing so jeopardizes the medium-term macroeconomic framework, and exposes the country to greater vulnerability in the face of external shocks and contingent liabilities.